Influence of soil and climate on root zone storage capacity. Issue 3 (16th March 2016) - de Boer‐Euser, Tanja; McMillan, Hilary K.; Hrachowitz, Markus; Winsemius, Hessel C.; Savenije, Hubert H. G.
Abstract: Root zone storage capacity ( Sr ) is an important variable for hydrology and climate studies, as it strongly influences the hydrological functioning of a catchment and, via evaporation, the local climate. Despite its importance, it remains difficult to obtain a well‐founded catchment representative estimate. This study tests the hypothesis that vegetation adapts its Sr to create a buffer large enough to sustain the plant during drought conditions of a certain critical strength (with a certain probability of exceedance). Following this method, Sr can be estimated from precipitation and evaporative demand data. The results of this "climate‐based method" are compared with traditional estimates from soil data for 32 catchments in New Zealand. The results show that the differences between catchments in climate‐derived catchment representative Sr values are larger than for soil‐derived Sr values. Using a model experiment, we show that the climate‐derived Sr can better reproduce hydrological regime signatures for humid catchments; for more arid catchments, the soil and climate methods perform similarly. This makes the climate‐based Sr a valuable addition for increasing hydrological understanding and reducing hydrological model uncertainty. Key Points: Plants develop their root systems to survive droughts Model root zone storage capacity ( Sr ) can be inferred from climate records Model experiment shows that Sr is stronger influenced by climate than by soil